The participation of nutritionists as a source of information for press articles related to obesity, published during the years 2008-2013 in Colombia (2017)
ABSTRACT: Background and objectives: Overweight and obesity are a public health problem in Colombia. By 2010 one in two colombians had one of these problems. One of the functions of the mass media is to mobilize society around this topics and is very important the participation of nutritionists as a part of the nutrition ed- ucation in these kind of communication channels. The aim of this paper is to describe the participation of nutritionists as a source of information supporting the publication of articles about obesity in newspapers during the years 2008-2013. Methods: Cross-sectional study. 163 news were selected from two newspapers; 48 from El Espectador and 115 from El Colombiano. A descriptive analysis was performed using X2 tests to establish the relationship between the variables of interest. α = 0.05. SPSS v.18.al characters, and 2% (n=1) of breakfast cereals, 16% (n=33) of cookies and 42% (n=21) of milk desserts included premium offers. Products with one excess nutrient (PAHO NP model) had significantly more promotional characters and premium offers (p<0.0005). Only 23% (n=9) without excess nutrients included promotional characters and 3% (n=1) included premium offers. Conclusions: Promotional characters and premium offers are used to promote unhealthy food products in Argentina. Evidence-based public health policies should restrict the use of these marketing techniques on products with high levels of sugars, fats and/or sodium, especially when children are exposed to them.